Influence of Arch Foot Defect of Primary Support on Mechanical Behaviors of an Arch Frame in Underground Tunnels. (8th March 2022) - Wang, Yakun; Guo, Junwei; Zhao, Jizeng; Yang, Xuxu; Li, Weiteng; Liu, Junfeng
Abstract : During the blasting excavation of the large-span tunnels, the instability of the blasting caused the overexcavation phenomenon, making the grille arch difficult to land completely in the primary support of the tunnel, thus forming an arch foot defect. In order to reduce the security issues of tunnel engineering construction and scientifically evaluate the influence of arch foot defects on the force performance of the overall structure of the arch frame, combining the Qingdao Metro long-span hard rock tunnel project, this paper designs two grille arch test sections with arch foot defects and one conventional section to carry out field tests. Combining with FLAC 3D numerical simulation, the results of the study were used for analyzing the stress characteristics of arch foot defect grille arch in the primary support of the tunnel. The results indicated that (1) the arch foot of conventional section arch frame is subjected to the force transferred from the upper part and the deformation pressure of surrounding rock within the arch foot range, and the upper transfer force borne by the arch foot mainly comes from the deformation of arch waist. (2) When the arch frame has arch foot defects, the deformation of surrounding rock at the arch foot and the deformation transferred from the upper part mainly depend on the shotcrete, thus resulting in the increase of shotcrete strain. (3) Anchoring bolt and shotcrete can integrate the grid arch with the surrounding rock, thus bearing local loads in the arch crown, arch waist, and shotcrete. (4) The numerical calculation of arch frame with arch crown, arch waist, and arch foot defects claims that the force reduction of the arch frame caused by the arch foot defect was the most obvious, and the calculation results were consistent with the actual project.